Trace Elements in Anaerobic Biotechnologies 2019
DOI: 10.2166/9781789060225_0073
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of trace-element supplementation

Abstract: Anaerobic digestion industries need to achieve higher performance and strive harder to play a key role in the green future of the energy sector. The importance of trace elements (TE) in the welfare of anaerobic bioreactors must be taken into account by the stakeholder/user to achieve these objectives. However, the implementation of a TE strategy is often stopped by its complexity, a lack of resource and the economic reality of a full-scale operating plant. The aim of this chapter is to support the translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Therefore each case of anaerobic digestion should be pretested, to determine the feasibility of adding the crude glycerol. Factors such as pH, temperature, redox potential, organic loading rate (OLR), hydraulic retention time (HRT), macronutrients, micronutrients, trace elements (TE), volatile fatty acids (VFA), ammonia, and electrical conductivity (EC) play an important role in the growth and activity of microorganisms (Roussel et al, 2019;Wyman et al, 2019). Recent studies have shown that microelements such as iron (Fe), zinc (Zn), chromium (Cr), copper (Cu), magnesium (Mg), nickel (Ni), manganese (Mn), barium (Ba), and others play an important role in the biogas production process (Schattauer et al, 2011;Wyman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore each case of anaerobic digestion should be pretested, to determine the feasibility of adding the crude glycerol. Factors such as pH, temperature, redox potential, organic loading rate (OLR), hydraulic retention time (HRT), macronutrients, micronutrients, trace elements (TE), volatile fatty acids (VFA), ammonia, and electrical conductivity (EC) play an important role in the growth and activity of microorganisms (Roussel et al, 2019;Wyman et al, 2019). Recent studies have shown that microelements such as iron (Fe), zinc (Zn), chromium (Cr), copper (Cu), magnesium (Mg), nickel (Ni), manganese (Mn), barium (Ba), and others play an important role in the biogas production process (Schattauer et al, 2011;Wyman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%